Hubungan Kadar Kreatinin Darah dengan Tekanan Darah pada Pasien Penyakit Ginjal Kronik Dengan Hipertensi di RSUD ODSK Provinsi Sulawesi Utara - Ivanna Delicia Barends; Diana Shintawati Purwanto; Youla Annatje Assa (Pusat riset dan Inovasi Nasional, 2026)
Chronic Kidney Disease (CKD) is a global health problem with a continuously increasing prevalence and mortality rate. Global data indicates that kidney disorders have affected more than 850 million people, with CKD being one of the leading causes of death. North Sulawesi is recorded as one of the provinces with the highest prevalence of CKD. Blood creatinine is used as the primary marker of kidney function, while hypertension is a comorbidity commonly found in CKD patients and can act as both a cause and a consequence of impaired kidney function. Several studies have reported varying results regarding the relationship between creatinine levels and blood pressure. Purpose to analyze the association between serum creatinine levels and blood pressure in chronic kidney disease patients with hypertension at ODSK Hospital, North Sulawesi Province. Methods the research design used an observational analytic cross-sectional design. This study used an observational analytic cross-sectional design. It was a retrospective study utilizing secondary data from medical records for the period of June 2022 to August 2025. Total sampling method was employed with a sample size of 65 patients who met the inclusion criteria. Based on the Spearman correlation test results, the significance values between creatinine and systolic pressure was 0.685, and between creatinine and diastolic pressure was 0.787 (p-value >0.05). There is no significant correlation between serum creatinine levels and blood pressure in chronic kidney disease patients with hypertension at ODSK Hospital, North Sulawesi Province.